Myoma pseudocapsule - a biological and surgical structure to respect during myomectomy - Tinelli Andrea; Sparić Radmila (Srpski Arhiv za Celokupno Lekarstvo, 2020)
Uterine fibroids affect almost one in two patients, causing many pelvic problems and requiring pharmacologic and surgical treatment. For many years, the importance of the fibroid was emphasized as uterine pathology, without focusing on the complex myometrial biology peripheral to fibroid. Moreover, the traditional surgical technique in fibroid removal has not been investigated for years. In recent years, on the contrary, morphological, neuroendocrine and anatomical studies have demonstrated the importance of a biological and surgical structure surrounding myoma, rich in neurotransmitters and neurofibres, the myoma pseudocapsule. This structure is formed in the womb peripheral to fibroid onset, it separates the fibroid from the myometrium and acts as a tissue regenerator after the removal of the fibroid from the uterus. The translation of scientific research on pseudocapsules into surgical practice has allowed us to identify new techniques of myomectomy, removing the myoma inside the pseudocapsule and promoting the pseudocapsules sparing surgery. All this to favor the subsequent biological process of uterine scarring and healing, by activating the neurotransmitters and neurofibres present in the myometrial fovea. The correct healing after fibroid removal restores the uterine anatomy, with a positive impact on subsequent reproductive function, reducing problems related to the muscle scar.